Penerapan kompetensi TI pada perpustakaan praktek kerja lapangan mahasiswa jurusan ilmu perpustakaan - Ade Abdul Hak (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2013)
This research is aim to describe the application of information technology competency at the libraries where the students of library department, Faculty of Adab UIN Syarif Hidatullah Jakarta, do the practical librarianship. In spite of that, it is to know that how the needs of them are viewed. The method of quantitative descriptive is used for analyzing the description of data from the LITA standard-based questioner. The LITA standard-based information technology competency is divided into 4 categories, namely: the basic knowledge of computer, the skill of internet, the hardware of computer, and the products of library automation. The result is viewed that the competency of the basic computer at the libraries is high (80%) while the needs is very high (93,3%). The competency of internet at the libraries is low (20%) while the needs isvery high (100%). The competency of the computer hardware is enough (55,6%) while the needs is very high (100%). The competency of library automation products is high (58,3%) while the needs is very high. Based on these, it is recommended that it’s needed some additional time or lecture for information technology competency in library curriculum.